Responding to the COVID-19 pandemic in Trinidad and Tobago: Challenges and opportunities for teacher education - Kalloo, Rowena Constance; Mitchell, Beular; Kamalodeen, Vimala Judy (Journal of Education for Teaching, 2020)
Trinidad and Tobago responded decisively to the COVID 19 pandemic and was successful in containing community spread of the virus. By mid-march 2020, there was closure of key business and educational institutions. To minimise the loss of learning time, emergency remote learning became the modus-operandi, a response which challenged the most socially vulnerable students. At the University of the West Indies (UWI) the 500 participants enrolled in the Early Childhood, and Primary education programmes, and the in-service post-graduate diploma in Secondary education were struggling to adjust to online teaching, the existential anxiety of coping with a dangerous disease, and programme completion. The UWI instituted a COVID-19 policy that facilitated a structured response to programme completion and assessment across all faculties.The paper analysed the decisions taken by the UWI School of Education that supported its teachers through the practicum and pedagogy courses. Using a qualitative case study methodology, data were collected through observations, documents, and informal discussions with faculty. Thematic analyses allowed the emergence of three key constructs that facilitated effective learning during the crisis period : Community as an empathetic connection to stakeholders, Creativity as the ability for agile and imaginative responses, and Connectivity through technological readiness.
Keywords: COVID-19; Teacher education; inequities; online education